FKUB’s Communication Strategy in Mantaining Religious Harmony in Medan - Fauji Wikanda; Mohd. Hatta; Abdullah Abdullah (Budapest International Research and Critics University, 2020)
The objective of this study is to investigate communication strategies implemented by Forum Kerukunan Umat Beragama (Indonesian: Religious Harmony Forum) in maintaining religious harmony in Medan. The research used a qualitative descriptive analysis and a method of data collection which consisted of indepth interviews with research informants, interviews using observation techniques with direct field observation, and document study to explore data. Communication strategies implemented by Forum Kerukunan Umat Beragama (FKUB) in maintaining religious harmony in Medan include determining communicators based on the communicants’ religion and ethnicity; grouping the target audience by adjusting the program’s theme to the communicants’ age, gender, education, work and religion; gathering informative, persuasive and educational messages; and utilizing printed, electronic and outdoor media.